The Influence of Spiritual Support on Anxiety Levels and Sleep Quality in Pre-Operative Patients : Literature Review - Setiyowati, Eppy; Zulkarnain, Eva Vera (Chakra Brahmanda Lentera Institute, 2024)
Background: Many types of stress psychology at hand on the patient before the operation Because every operation has different stressors, such as: Anxiety, fear or worries about the perception of the patient's operation. One of the intervention For lower anxiety and increased quality Sleep preoperative patients is with give spiritual support (audio visual) in the form of murotal Qur'an for religious patients Islam and singing spiritual for religious patients Christian . Objective from this literature review is For know exists the influence of spiritual support on level anxiety and quality Sleep preoperative patients . Methods: Method used in article This that is PRISMA Approach-literature review with using a journal database from science direct , pubmed , and google scholar in range time 2019-2023 with the keywords spiritual support , anxiety and quality Sleep . Results: From the identification results based on inclusion criteria and eligibility review, ten articles were obtained for review. Studies literature review obtained results that There is influence significant anxiety and quality sleep in patients who get spiritual support with those who don't get spiritual support. Conclusion: Spiritual Support may be recommended in the preoperative process in the hospital to reduce anxiety